The Motivation of Students and Their Exposure to Learning Loss After the Pandemic - Abd. Syakur; Wahyu Sudrajad; Sutri Winurati; Shouket Ahmad Tilwani (Studies in Learning and Teaching, 2023)
This research seeks to illustrate how the COVID-19 epidemic has affected students' motivation, engagement, and learning. Students had learning difficulties during the pandemic, as demonstrated by their nonattendance in online courses and their inability to turn in homework on sites such as Google Classroom. Acknowledging these difficulties, the instructor made house calls to collect information for this study. By exposing 100 ninth-grade students to several, the researcher addressed learning loss. The study used a case study methodology and included both qualitative and quantitative data. Google Forms was used to conduct both closed- and open-ended surveys for data gathering. According to the results, just 20.6% of students reported having no learning loss during the pandemic, compared to 79.4% who reported having it. Students' trust in their learning experiences throughout the pandemic was divided into three categories: great certainty (33.4%), certainty (46%), and uncertainty (20.6%). Furthermore, based on their comments on Google Forms, the data revealed that 52.5% of students thought their learning experience was bad, 28.2% thought it was extremely weak, and 19.6% thought it was strong.